Impact of disease progression on health-related quality of life in patients with metastatic breast cancer in the PRAEGNANT breast cancer registry. (February 2018) - Müller, Volkmar; Nabieva, Naiba; Häberle, Lothar; Taran, Florin-Andrei; Hartkopf, Andreas D.; Volz, Bernhard; Overkamp, Friedrich; Brandl, Anna Lisa; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Ettl, Johannes; et al.
Abstract: Objectives: Improved progression-free survival is considered as treatment goal for patients with metastatic breast cancer (MBC) since it is assumed to delay or prevent deterioration of quality of life. Aim of our analysis was to examine the influence of disease progression on health-related quality of life (HRQoL). Materials and methods: The PRAEGNANT study comprises a real-life registry for patients with MBC. HRQoL was assessed with the EORTC-QLQ-C30 Version 3.0 questionnaire at study entry and every 3 months thereafter. The primary endpoint was minimally important deterioration (MID) in global HRQoL score by ≥ five points between baseline and any follow-up assessment. A logistic regression model was built with MID (yes/no) at a follow-up timepoint as outcome variable and several covariates as predictors. Results: In total, 329 patients were included in this analysis, with disease progression in 63 patients. Concerning the primary study aim, progression status predicted MID of global HRQoL status in addition to the other covariates. The adjusted odds ratio for the effect of progression status on MID was 2.22 (95% CI: 1.04 - 4.73). Comparisons of mean differences of QoL domains/scales yielded no differences. Conclusions: We provide evidence that disease progression in patients with metastatic breast cancer in a real-world registry has a significant negative impact on HRQoL as measured by MID of HRQoL. This study emphasizes the relevance of avoiding progression and prolonging PFS to maintain QoL. Highlights: Disease progression in patients with metastatic breast cancer has a negative impact on HRQoL. Delaying disease progression is therefore a relevant aim of therapeutic interventions. Quality-of-life assessments should be implemented in breast cancer registries.